1999
DOI: 10.1016/s0022-5223(99)70152-2
|View full text |Cite
|
Sign up to set email alerts
|

Superior protection in orthotopic rat lung transplantation with cyclic adenosine monophosphate and nitroglycerin–containing preservation solution

Abstract: Background: Primary lung graft failure is common, and current lung preservation strategies are suboptimal. Because the decline in lung levels of cyclic adenosine monophosphate and cyclic guanosine monophosphate during preservation could enhance adhesiveness of endothelial cells for leukocytes as well as increase vascular permeability and vasoconstriction, we hypothesized that buttressing these levels by means of a preservation solution would significantly improve lung preservation. Methods: An orthotopic rat l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 30 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…This observation has led to new approaches in organ preservation ± the preservation period can be exploited to buttress the preservation solution in a way that helps maintain the homeostasis not only of functional cells, but also of the vasculature within the graft. Antisense strategies [22] or strategies to buttress vascular regulatory cyclic nucleotide second messengers [86] are highly effective in experimental animal models of lung transplantation, and await clinical testing.…”
Section: Organ Transplantation As a Model Situationmentioning
confidence: 99%
“…This observation has led to new approaches in organ preservation ± the preservation period can be exploited to buttress the preservation solution in a way that helps maintain the homeostasis not only of functional cells, but also of the vasculature within the graft. Antisense strategies [22] or strategies to buttress vascular regulatory cyclic nucleotide second messengers [86] are highly effective in experimental animal models of lung transplantation, and await clinical testing.…”
Section: Organ Transplantation As a Model Situationmentioning
confidence: 99%
“…The base preservation solution consisted of saline with heparin (100 U/mL) alone or with the following additional reagents: N 6 ,2'-O-dibutyryl adenosine 3':5'-cyclic monophosphate (db-cAMP; 2 mmol/L); 8-bromoadenosine-cAMP (8-Br-cAMP; 0.1 mmol/L); and 8-Br-cAMP (0.1 mmol/L) plus Rp-cAMPS (0.25 mmol/L), the Rp isomer of adenosine 3',5'-monophosphate (Sigma). 16 The concentrations of these cAMP analogues have been shown to be the optimal dose on the basis of previous studies, 12,13,16 and adding cAMP analogues did not change the acidity of the base preservation solution.…”
Section: Graft Preservationmentioning
confidence: 87%
“…[9][10][11][12] Ischemia-driven cAMP deficiency in preserved organs is a critical mechanism by which vascular homeostasis might be disrupted. 9,[11][12][13][14] This study was designed to test the hypothesis that initial ischemic insult during harvest and storage of vein grafts is a central factor in the development of neointimal hyperplasia and that enhancement of graft preservation through supplementation of the cAMP pathway might attenuate vein graft neointimal hyperplasia.…”
mentioning
confidence: 99%
“…Studies reveal that the result of these additives is to provide an overall quality of lung preservation similar to that achieved by modified Euro-Collins solution but with the tolerance of much longer periods of ischemia.58 Columbia University has reported improved preservation using another solution having an intracellular composition as well as the addition of substances that confer beneficial effects by preserving vascular endothelial homeostasis and integrity. 59 These investigators hypothesized that a decline in lung levels of cyclic adenosine and guanosine monophophates during preservation resulted in enhanced endothelial cell adhesiveness for leukocytes, increased vascular permeability, and vasoconstriction. By buttressing levels of these mediators with their preservation solution, which contains a cyclic monophospate analog, they found that these deleterious effects are ameliorated.…”
Section: Donor Criteria and General Conduct Of The Harvestmentioning
confidence: 99%